Psychometric study of the forgiveness in divorce-separation questionnaire [Estudio psicométrico del cuestionario de perdón en el divorcio-separación] - Castilla-Cabello, Humberto (2020)
ABSTRACT The objective was to analyze the psychometric properties of reliability and validity of the questionnaire Forgiveness in Divorce-separation (CPD-S), of Yárnoz-Yaben and Comino (2012). The sample consisted of 203 college students, men (25.1%) and women (74.9%), who had an experience of love couple, aged between 16 and 32 years old with an average age of 20.51 years (SD = 3.375), in order to obtain evidence to support its use in the city of Lima. Correlation analysis item-test found highly significant associations (p <0.001) for each of the items, indicating that the reagents evaluated indicators same construct. The questionnaire has acceptable internal consistency (Cronbach’s α= .720). Also, the evaluation of bias by comparing coefficients Alfa suggests absence. Evidence of convergent and predictive validity was obtained of questionnaire. Finally, to analyze the factor structure, an exploratory factor analysis where the result of the KMO test casts doubt on the feasibility of such analysis. Based on the results obtained states that the validity of the CPS is inconclusive. Keywords: reliability, partner, forgiveness separation, validity.